2017
DOI: 10.1039/c7dt01970j
|View full text |Cite
|
Sign up to set email alerts
|

Co-Doped Zn1−xCdxS nanocrystals from metal–organic framework precursors: porous microstructure and efficient photocatalytic hydrogen evolution

Abstract: Nanoporous Co-doped ZnCdS were facilely fabricated via adopting ZIFs as templates, and Cd(NO) and thiourea as precursors. The highly porous microstructure and uniform Co-doping of the photocatalyst afford a high H-production rate (45.2 and 422.2 times larger than those of ZnCdS and CdS), providing an effective way for the development of high performance nanoporous photocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…In general, two emissions comprising excitonic and trapped photoluminescence are observed from semiconductor nanomaterials. 21,31 In theory, the excitonic emission is sharp and found close to the absorption edge, while the trapped emission is broad and found at a longer wavelength. In this study the as-synthesized CdS showed the PL emission spectrum over the range of 540-660 nm.…”
Section: Photoluminescence Studymentioning
confidence: 95%
See 3 more Smart Citations
“…In general, two emissions comprising excitonic and trapped photoluminescence are observed from semiconductor nanomaterials. 21,31 In theory, the excitonic emission is sharp and found close to the absorption edge, while the trapped emission is broad and found at a longer wavelength. In this study the as-synthesized CdS showed the PL emission spectrum over the range of 540-660 nm.…”
Section: Photoluminescence Studymentioning
confidence: 95%
“…15,35 In contrast, it has been reported that the degradation of RR141 can be achieved by using CdS photocatalyst under visible light irradiation. 21 However, it does take longer time, i.e., about 240 min to reach 95% degradation.…”
Section: Photocatalytic Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the above mentioned examples there are other MOF derivatives explored for photocatalytic H 2 production that include Ni 2 P/CdS composite derived from Ni‐BTC (BTC=1,3,5‐benzenetricarboxylic acid) MOF, yolk‐shell CdS microcubes synthesized from Cd−Fe Prussian blue analogues (Cd−Fe‐PBA), porous CdS, MOS 2 @TiO 2 catalyst derived from NH 2 ‐MIL‐125, Pd decorated TiO 2 using NH 2 ‐MIL‐125, ZIF8derived Ndoped graphene analogous polyhedrons (ZNGs), Co doped Zn‐Cd‐S Nanocrystals,Co 3 O 4 /TiO 2 p‐n heterojunction using Co‐based MOF mesoporous Cu/CuO@TiO 2 nanocomposite using Cu‐MOF and titania supported Cu‐Cu 2 O nanoparticle derived from MOF‐199 ([Cu 3 (BTC) 2 (H 2 O) 3 ] n …”
Section: Mofs For Hydrogen Productionmentioning
confidence: 99%